ANALISIS RASIO LIKUIDITAS SOLVABILITAS DAN AKTIVITAS UNTUK MENGUKUR KINERJA KEUANGAN (JURNAL ECONOMICA : Research of Economic And Economic Education, 2018)
ABSTRACT The purpose of this study is to analyze the ratio of liquidity, solvency and activity for the measurement of financial performance. Data analysis method is comparative descriptive analysis. From the bank financial statements then analyzed the liquidity, solvency, activity, and profitability for comparison of results in each year and will be adjusted to Bank Indonesia (BI) standard that can be analyzed to measure what the financial level and performance of the bank. While the data source used in this study is secondary data in the form of bank financial statement documents from 2012 to 2016 obtained from the website www.idx.co.id. The results show, bank liquidity is able to meet the short term in a timely manner. The result of solvency is seen ability of bank in fulfilling and keeping its ability to always able to fulfill its obligation in paying debt in a timely manner. Maximally maximized resource viewing activity results. The profitability of banks has a good ratio. Key word: analysis, financial statement, financial perfomance